(untitled) (American Journal of Interdisciplinary Research and Development, 2025)
Nowadays, the process of widespread integration of digital technologies into Uzbekistan’s education system is actively underway. The use of electronic textbooks, distance learning platforms, and modern technological tools in schools is bringing the educational process to a qualitatively new level.